TINJAUAN PEMAHAMAN NILAI-NILAI SYARIAH BAGI KARYAWAN PADA PT. BANK MUAMALAT INDONESIA, Tbk. CABANG KENDARI - Kusmiati, Kusmiati; Nandawijaksana, Dwi Angga (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
Abstract This study aims to determine how the understanding of Islamic values to employees at PT. Bank Muamalat Indonesia, Tbk. Kendari branch. Data collection techniques performed in this research is by using primary data by conducting interviews and filling the questionnaire (questionnaire) were distributed to a total of 12 questionnaires and using descriptive statistical analysis. From the results of this study indicate that employees understanding of PT. Bank Muamalat Indonesia, Tbk. branch Kendari on Values Sharia based outlined in indicators Instrumental, Socio-Economic, Critical, Justice, All-Incluisive, Rational-Intuitive, Etichal, and Holistice Welfare which is illustrated by a pie chart that variable Humanist and emancipatory was very good, this is consistent with the average percentage of respondents by 83%, and 81 are at a scale of 81% - 100% with the criteria very well. While based on the Transcendental variables and Teleologikal is good, this is in accordance with the average percentage of 80% of respondents are at a scale of 61% - 80% with good criterion.Keywords: Quran, Islamic values, understanding.